Fabrication of novel 1D/2D V2O5/g-C3N4 composites as Z-scheme photocatalysts for CR degradation and Cr (VI) reduction under sunlight irradiation. Issue 1 (February 2019) - Dadigala, Ramakrishna; Bandi, Rajkumar; Gangapuram, Bhagavanth Reddy; Dasari, Ayodhya; Belay, Hadgu Hailekiros; Guttena, Veerabhadram
Graphical abstract: Highlights: V2 O5 nanorods/g-C3 N4 nanosheet (VONRs/CNNs) composites were constructed by an impregnation method. 4 wt% VONRs/CNNs exhibited high photodegradation of Congo Red and photoreduction of Cr (VI) under sunlight irradiation. The enhanced photocatalytic activity was mainly due to the synergistic effect of heterojunctions. VONRs/CNNs composites exhibited excellent stability and reusability. A Z-scheme photocatalytic mechanism was proposed for VONRs/CNNs composites. Abstract: Photocatalytic materials for environmental remediation of organic pollutants and heavy metals require not only a strong visible light response and high photocatalytic performance, but also the regeneration and reuse of catalysts. In this work, 1D/2D V2 O5 nanorods/g-C3 N4 nanosheets (VONRs/CNNs) composites were prepared by a facile impregnation method and employed in the degradation of a Congo red (CR) and reduction of Cr (VI) under sunlight irradiation. The as-prepared samples were studied by several characterization techniques including XRD, SEM, TEM, EDS, XPS, FTIR, UV–vis DRS and PL. Results revealed that the interface interaction between VONRs and CNNs was recognized via V2 O5 nanorods loading on the surface of g-C3 N4 nanosheets, improving the separation and transfer of photogenerated electron-hole pairs and restraining the recombination rate of charge carriers. As a result, the photocatalytic activity of the composites was enhanced in comparison with pure CNNs and VONRs. The photocatalytic efficiency of optimal composite (4-VONRs/CNNs) for the removal of CR (Cr (VI)) was about 9.33 (4.22) and 73.52 (19.2) times higher than that of pure CNNs and VONRs, respectively. Meanwhile, the 4-VONRs/CNNs exhibited good photocatalytic stability in recycling experiments. Such enormous enhancement in photocatalytic performance was predominantly ascribed to the efficient separation and transfer of photogenerated electron-hole pairs at the VONRs/CNNs interface imparted through the direct Z-scheme charge carrier migration mechanism. Moreover, the energy band structure and the quenching effects of different scavengers demonstrated that the electrons of CNNs and holes of VONRs with higher oxidizability and reducibility are the real participants in photocatalytic reactions.